Penegakan Hukum Luar Biasa Atas Kejahatan Ekosida Sebagai Extraordinary Crime Dalam Konsep Hukum Lingkungan Internasional - Siti Khairunnissa; Fajar Khaify Rizky; Siti Nurahmi Nasution; Boy Laksamana (Riau Law Journal, 2022)
The quality of the environment is the most important part of human life in dignity and humility. In practice, ecocide are mostly committed by corporations, both national and transnational. Environmental crimes that are structured and systematic or often called ecocide do not concern as an extraordinary crimes. The International Criminal Court (ICC) has proposed to several countries such as Fiji, Vanuatu, and the Maldives that the need to add elements as international criminal crimes categorized as extra ordinary crimes in the Rome Statute and recognized as the fifth type of crime that becomes the jurisdiction of the International Criminal Court for trial. The purpose of this research is as a contribution to answer question. First, to analyze and to understand in developing extraordinary law enforcement against the crime of ecocide as extraordinary crime. Second, law enforcement review against ecocides in various regulations and various court decisions in Indonesia Third, to analyze the concept of international environmental law in the extraordinary enforcement law against ecocide crimes (Extra ordinary Crime) The research method used by researchers is normative juridical approach. This means that the legal material used as a study is secondary data. In this normative legal research it is not closed the possibility that empirical data (field) is also presented as an option to support and sharpen the study